Memory and heritage in the history of education: possibilities and challenges - Alexandra Lima da Silva; Evelyn de Almeida Orlando (Universidade Federal de Uberlândia, 2019)
This article discusses the uses of memory and heritage concepts in the field of history of education. From making a balance on the main contributions of studies on national and international levels on the memory and educational heritage subject (NORA, 1993. LE GOFF, 1990), it highlights the concern with the school material culture as historiographical object (JULIÀ, 2011). The looks into this heritage issue, however, are cast not only considering the size of the school, but also its movement to other areas of the city that, in their potentiality, impose themselves as educational signs and educational heritage (ARROYO, 2005). In this relation, we sought to draw attention to the intangible heritage, yet little studied in educational historiography (FONSECA, 2003). The article concludes that exploring the richness of the doings, knowledge and practices is a challenge to be faced in the history of education field.